A novel in vivo impact device for evaluation of sudden limb loading response. Issue 1 (January 2015) - Boutwell, Erin; Stine, Rebecca; Gard, Steven
Highlights A novel in vivo testing apparatus was developed to study limb loading. Mechanical reliability and human subject data were collected. Impact forces in human subject testing were comparable to those found in walking. High repeatability of impact forces were achieved within both data sets.